Online Counseling on Global Issues: Systematic Literature Review - Ifdil, Ifdil; Zatrahadi, Muhammad Fahli; Darmawati, Darmawati; Istiqomah, Istiqomah; Bakar, Abu Yazid Abu (Society of Visual Informatics, 2025)
The integration of expertise in counseling with a deep comprehension of contemporary technology is essential. Developing a sustained method is crucial for creating a practical framework to address the psychological ramifications associated with the escalating complexities of global challenges. Therefore, this study was conducted to explore the use and challenges of online counseling (e-counseling) for global issues using the systematic literature review (SLR) method. The search was carried out in the Scopus database to obtain 637 documents after limitations in the year of publication, starting in 2020–2023. Another limitation was the use of the English language, and after quality assessment, a 25-article document analysis was conducted. The results showed that e-counseling was critical in addressing challenges and impacted many individuals in different regions. According to NVivo analysis, the practical implementation of online counseling (e-counseling) encountered several challenges, such as using potentially vulnerable technology, constraints within interpersonal relationships, and incorporating different methods.